Anatomic Anterior Cruciate Ligament Reconstruction: Current Concepts and Future Perspective. (July 2013) - Murawski, Christopher D.; Wolf, Megan R.; Araki, Daisuke; Muller, Bart; Tashman, Scott; Fu, Freddie H.
Anatomic anterior cruciate ligament (ACL) reconstruction is common procedure performed by orthopedic surgeons, particularly in association with sports-related injuries. Whereas traditional reconstruction techniques used a single bundle graft that was typically placed in a non-anatomic position, a renewed interest in anatomy has facilitated the popularization of anatomic reconstruction techniques. Recently, a focus has been placed on individualizing ACL surgery based on each patient's native anatomical characteristics (e.g., insertion site size, notch size, and shape), thereby dictating the ultimate procedure of choice. As subjective outcome measurements have demonstrated varying outcomes with respect to single- versus double-bundle ACL reconstruction, investigators have turned to more objective techniques, such as in vivo kinematics, as a means of evaluating joint motion and cartilage contact mechanics. Further investigation in this area may yield important information with regard to the potential progression to osteoarthritis after ACL reconstruction, including factors affecting or preventing it.